Бідність в Україні у показниках соціальної статистики - Хомяк, Марія Ярославівна; Хомяк, Мария Ярославовна; Khomiak, Mariia Ia. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Розглянуто основні концепції об’єктивного оцінювання бідності. Наведено кількість бідних в Україні відповідно до різних методик вимірювання. Зокрема, згідно з абсолютною концепцією бідності відповідно до міжнародних критеріїв, запропонованих ООН, 2,9 % українців вважаються бідними; за критерієм прожиткового мінімуму – 9,9 %; а за відносним критерієм бідних в Україні 26 %. Проте практичне використання об’єктивних оцінок бідності має певні недоліки, головний із яких – складність отримання своєчасної, повної та достовірної інформації щодо рівня доходів, витрат і наявних ресурсів домогосподарств. The essence and types of poverty are defined. The basic methods of objective assessment of poverty and the main their shortcomings are considered. The numbers of poor citizens in Ukraine according to the different methods of measurement are given. In particular, due to the concept of absolute poverty according to international criteria proposed by the UNO 2,9 % Ukrainians are considered poor. By the criterion of the minimum subsistence level 9,9 % are poor. By the relative criterion there are 26 % of poor Ukrainians. The main disadvantages of relative and absolute poverty are given. The conclusion about the practical use of objective assessments of poverty is done. The main of its drawbacks are the difficulties of obtaining timely, complete and accurate information on income, expenditure and available household’s resources. Particularly the issue is sensitive when it comes to research level and sources of income in the case of existing of the strong black sector that is characteristic for modern Ukraine.
Poverty In Ukraine In Terms of Social Statistics
Keywords: рівень бідності; абсолютна бідність; відносна бідність; споживчий кошик; межа бідності; poverty level; absolute poverty; relative poverty; consumer basket; poverty line